Electrochemical Synthesis of High Chromium Fe-Based TiC Composite Coating - Demiroren, Hulya; Buytoz, Soner (Maik Nauka/Interperiodica/Springer, 2022)
In order to investigate the effect of M7C3 and TiC carbides on electrochemical synthesis behavior of Fe-Cr-C and Fe-Cr-C/TiC coatings, Fe-based composite layer was prepared on medium carbon steel surface by using tungsten inert gas coating technique. The microstructure and phase structure of the coatings were analyzed by optical microscope with clemex image analyse, scanning electron microscope (SEM) equipped with an energy-dispersive spectroscopy (EDS) and X-ray diffractometer (XRD). The samples were exposed EIS (electrochemical impedance spectroscopy) method in sea water. Frequence diagrams and Nyquist diagrams were obtained. As a result, adding TiC improved the electrochemical behavior of FeCrC coating.
Keywords: Fe-based composite; M7C3 carbide; TiC carbide; EIS; Nyquist plot